Wheat Cost-Return Budget in South Central Kansas - O'Brien, Daniel M.; Shoup, Douglas; Ibendahl, Gregg (My University, 2015)
This publication projects a budget that reflects expected income and costs based on wheat production in south central Kansas.
MF574_2015_04
Keywords: MF574; Economics; Crops; MF